Humanistic perspectives in virtual reference. Issue 8 (27th October 2017) - Prieto, Adolfo G.
Abstract : Purpose: Virtual reference is a part of the services offered at academic and other types of libraries. This paper discusses humanistic perspectives that merit consideration in the provision of virtual reference (VR), including mindfulness, authenticity, emotional intelligence (EI) and counseling. This study aims to make these perspectives become a part of the language and practice of virtual reference through this discussion. Design/methodology/approach: The paper establishes a framework for the VR perspectives it discusses by examining relevant literature for background information and practical applications. Findings: VR has the potential to benefit from the interrelated humanistic perspectives of mindfulness, authenticity, EI and counseling. It is through the counseling perspective that mindfulness, authenticity and EI are embodied to offer a more transformational and less transactional experience for both librarians and users. Research limitations/implications: While the paper provides examples of language used by the author to illustrate the counseling perspective, a future study, whereby virtual reference transcripts are formally analyzed, may be beneficial to determine other expressions of counseling and its related perspectives of mindfulness, authenticity and EI. Practical implications: This paper provides a resource especially helpful to individuals new to VR or who seek opportunities for growth in providing VR. Originality/value: In addition to taking a multifaceted view of VR through the humanistic perspectives presented, this paper also offers a multidisciplinary approach in its discussion, drawing from areas such as business and medicine.